RESPON SISWA TERHADAP IMPLEMENTASI QUIZIZZ SEBAGAI MEDIA EVALUASI ONLINE DALAM PEMBELAJARAN TARAKIB BAHASA ARAB DI MTs DARUL ULUM TULANGAN - Anggraini, Rishka; Anwar, Najih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine students’ responses to the implementation of Quizizz as an online evaluation media in Tarakib learning. This study employed a descriptive quantitative approach using a Likert scale-based closed questionnaire as an instrument, which was distributed to 74 students in grades VII, VIII, and IX. The data were analyzed using a percentage technique based on five indicators, namely fun and involvement, ease of access, understanding of the material, clarity of instructions, and speed of feedback. The result showed that students’ responses to the use of Quizizz were in the very positive category with an average percentage of 90,56%. This finding shows that Quizizz can increase student involvement, understanding, and motivation in learning tarakib. Therefore, the implementation of Quizizz can be used as an alternative evaluation media that is effective, interactive, and fun to improve the quality of Arabic language learning.